Acetate overflow metabolism regulates a major metabolic shift after glucose depletion in Escherichia coli. Issue 15 (30th June 2021) - Shimada, Tomohiro; Nakazawa, Kohta; Tachikawa, Tomoyuki; Saito, Natsumi; Niwa, Tatsuya; Taguchi, Hideki; Tanaka, Kan
Abstract : Acetate overflow refers to the metabolism by which a large part of carbon incorporated as glucose into Escherichia coli cells is catabolized and excreted as acetate into the medium. We previously found that mutants for the acetate overflow pathway enzymes phosphoacetyltransferase (Pta) and acetate kinase (AckA) showed significant diauxic growth after glucose depletion in E. coli . Here, we analyzed the underlying mechanism in the pta mutant. Proteomic and other analyses revealed an increase in pyruvate dehydrogenase complex subunits and a decrease in glyoxylate shunt enzymes, which resulted from pyruvate accumulation. Since restoration of these enzyme levels by overexpressing PdhR (pyruvate‐sensing transcription factor) or deleting iclR (gene encoding a pyruvate‐ and glyoxylate‐sensing transcription factor) alleviated the growth lag of the pta mutant after glucose depletion, these changes were considered as the reason for the phenotype. Given the evidence for decreased coenzyme A (HS‐CoA) levels in the pta mutant, the growth inhibition after glucose depletion was partly explained by limited availability of HS‐CoA in the cell. The findings provide insights into the role of acetate overflow in metabolic regulation, which may be useful for biotechnological applications. Abstract :